2016
DOI: 10.1007/s41061-016-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Calix-Based Nanoparticles: A Review

Abstract: Calixarenes are considered as third generation supramolecules with hollow cavity-like architecture whereas nanoparticles are small entities with dimensions in the nanoscale. Many exciting achievements are seen when the calix system merges with nanoparticles which produces many fascinating facets in all fields of contemporary chemistry. The properties of nanoparticles which are tuned by calixarenes find applications in sensing, catalysis, molecular recognition, etc. Here, we have reviewed the chemistry of calix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 104 publications
0
29
0
Order By: Relevance
“…[2][3][4] As a result, this class of compounds has been exploited for different tasks, such as catalysis, ion extraction, [5] purification, [6] electrochemical and fluorimetric sensing, [7,8] etc. In recent advancements the potentials of calixarene based compounds as biomimetics, drugdelivery systems, [9] ion chanells, [10,11] nanomaterial components [12,13] etc. have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] As a result, this class of compounds has been exploited for different tasks, such as catalysis, ion extraction, [5] purification, [6] electrochemical and fluorimetric sensing, [7,8] etc. In recent advancements the potentials of calixarene based compounds as biomimetics, drugdelivery systems, [9] ion chanells, [10,11] nanomaterial components [12,13] etc. have been explored.…”
Section: Introductionmentioning
confidence: 99%
“…It's known, that AgNPs possess unique optical, electronic and biological properties [1,16], that allows to expand their application in emerging fields, such as anticancer agents, drug delivery or diagnosis [17]. Recently different families of supramolecular macrocycles (cyclodextrins, cucurbit[n]urils, pillar[n]arenes, and calixarenes) have been used as capped agents for metal nanoparticles [18,19]. Such hybrid nanoparticles combine the properties of metal nanoparticles (optical, antibacterial and other) and the receptor properties of macrocycles and demonstrate enhanced sensory [20][21][22][23][24][25][26][27][28][29] and biological [30][31][32] properties.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic accessibility and receptor properties of calix [4]resorcinarenes make them promising candidates as a capped agents for metal nanoparticles, in particular AgNPs. Earlier some examples of calix [4]resorcinarenes-capped metal NPs hydrosol were reported [19,[38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Taking the advantage of this versatile ion-recognition property of the thiacalixarenes, it was incorporated as a reducing and stabilizing agent in the nano system. Calix based nanoparticles have found versatile applications in all contemporary fields of science [20]. Tu et al have reported the preparation of size-controlled gold nanoparticles using amphiphilic thiacalixarene derivatized with a hydrophilic tail, namely, poly(ethylene glycol) monomethyl ether (SCaQ-MPEG550) [21].…”
Section: Introductionmentioning
confidence: 99%